Emergences and possibilities about of University Research and Innovation - Teresa García Gómez; Eduardo Fernández Rodríguez (Revista Interuniversitaria de Formación del Profesorado)
This issue of the Revista Electrónica Interuniversitaria de Formación del Profesorado (REIFOP) offers a range of researchs, action and innovation projects thought to the Mass Communication Media and the Especific Didactics area.The authors of the articles are university professors who carry out their academic activity at Spanish and Foreing universities: Valladolid, Valencia, Piura, San Sebastián, Zaragoza, Soria, Kennesaw, Badajoz y Huelva.